Group B Streptococcus screening with antenatal culture and intrapartum polymerase chain reaction: A prospective cohort study - Marlene Samantha Sze Minn Goh; Hong Ying Tan; Yan Shun Ng; Ilka Tan; Kee Thai Yeo; Chee Wai Ku; Manisha Mathur (Annals, Academy of Medicine, Singapore, 2024)
Group B Streptococcus (GBS) is a common genital and gastrointestinal tract commensal in healthy women. Vertical transmission of GBS may cause neonatal early-onset GBS disease (EoGBS), and this is prevented by intrapartum antibiotic prophylaxis (IAP) GBS colonisation,1 coupled with long turnaround time of GBS culture, challenges the accuracy of conventional antenatal GBS screening in predicting carriage during labour, especially for those without prior antenatal GBS screening. Polymerase chain reaction (PCR) offers a rapid and accurate alternative, demonstrating 98.5% sensitivity and 99.6% specificity, surpassing the 58.3% positive predictive value of antenatal culture screening in a retrospective study,2 resulting in the reduction of EoGBS from 1.01 to 0.21 per 1000 live-births. This study aimed to compare the sensitivity and specificity of intrapartum GBS PCR to antenatal GBS swab culture, using intrapartum GBS culture as a reference for maternal colonisation status.